Challenges and constraints to the sustainability of poultry farming in Republic of Korea - Sidong Kim (Animal Bioscience)
As of 2022, the Republic of Korea accounted for 0.8% of global chicken meat production and 0.9% of global egg production. The country achieved self-sufficiency rates of 83.1% for chicken meat and 99.4% for eggs, demonstrating significant quantitative and qualitative growth to meet domestic demand. Although the industry is trending towards expansion and specialization, it faces several challenges in achieving sustainable poultry production. Key challenges in Korea include highly pathogenic avian influenza and pest issues, climate change and the push for carbon neutrality, reliance on imported breeding stock, insufficient preparedness for expanding cage space per laying hen, post-settlement payment systems for egg sales and an oversupply of chicken meat, and the aging poultry farming population and the closure of farms unable to secure successors. Following strategies are proposed to overcome or mitigate challenges mentioned above: (1) enhancing farm biosecurity and implementing vaccination policies for disease control, (2) modernizing facilities and promoting carbon-neutral practices to adapt to climate change, (3) diversifying breeding stocks across multiple locations and developing domestic strains, (4) implementing policies and supporting farms based on a comprehensive readiness assessment of all farms regarding expanded cage space requirements, (5) improving market transparency for the egg industry and regulating supply and demand in the broiler industry, and (6) offering incentives for farm succession, attracting labor, and promoting coexistence between corporations, rural communities, and small farms. In conclusion, the sustainable development of Korea's poultry industry is not a simple task. It requires a comprehensive approach considering economic efficiency, animal welfare, environmental protection, food security, and the symbiosis with rural communities. This approach necessitates efficient cooperation among all stakeholders, including the government, farmers, integrators, retailers, and research institutions, along with a comprehensive, phased strategy for both short- and long-term goals.